Macroeconomic change, competitiveness and timber production: a five-country comparison - Wunder, Sven (2005)
This study analyzes how long-run macroeconomic fluctuations have affected timber production levels in five tropical oil-producing countries: Gabon, Cameroon, Papua New Guinea (PNG), Venezuela, and Ecuador. The core hypothesis is that oil booms, foreign borrowing and other major foreign exchange inflows slow down timber harvesting. These inflows cause “Dutch Disease,” depressing the price competitiveness of timber exports and other trade-exposed sectors. A qualitative examination of long-run trends in the five countries is combined with simple econometrics. The findings confirm a strong impact of competitiveness on logging. Substantial real currency devaluation can greatly accelerate timber exports. Yet, in middle-income countries with strongly expanding domestic timber markets (Ecuador, Cameroon, Venezuela), home-market demand also rises much with urban incomes and population. When full or partial import protection occurs, this translates into rising domestic production. The relative weight of these two potentially significant factors varies widely, so policies to influence extraction levels need to be tailored accordingly.